2020
DOI: 10.1016/j.jsams.2019.08.294
|View full text |Cite
|
Sign up to set email alerts
|

Exercise in the first week following concussion among collegiate athletes: Preliminary findings

Abstract: Objective: Our purpose was to examine the association between exercise after concussion with symptom severity, postural control, and time to symptom-resolution. Design: Longitudinal cohortMethods: Collegiate athletes (n=72; age=20.2±1.3 years; 46% female) with concussion completed a symptom questionnaire at initial (0.6±0.8 days post-injury) and follow-up (2.9±1.4 days post-injury) evaluations, and a postural control assessment at follow-up. Participants were grouped into those who exercised in between the tim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 32 publications
0
18
0
Order By: Relevance
“…VOM function is required to complete academic activities (55), and the results of this study support this notion due to an association of greater academic impact in the presence of VOM impairment and academic time loss. One should also be aware these studies followed a different RTP protocol where physical exercise could resume after 48 hours if symptoms allowed, furthermore, resuming physical exercise has been associated with a quicker recovery (56). Future studies, with larger participant numbers may help to clarify if the use of VOMS at 4 days and after is able to determine if a student-athlete may have a delayed RTP.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…VOM function is required to complete academic activities (55), and the results of this study support this notion due to an association of greater academic impact in the presence of VOM impairment and academic time loss. One should also be aware these studies followed a different RTP protocol where physical exercise could resume after 48 hours if symptoms allowed, furthermore, resuming physical exercise has been associated with a quicker recovery (56). Future studies, with larger participant numbers may help to clarify if the use of VOMS at 4 days and after is able to determine if a student-athlete may have a delayed RTP.…”
Section: Discussionmentioning
confidence: 99%
“…This removes them from their usual sporting activities, which has been shown to be detrimental to health and wellbeing (58). VOM rehabilitation has shown promise in assisting recovery (59) and emerging data suggests resuming aerobic exercise within subsymptom threshold can enhance recovery (56,(60)(61)(62). There are currently no studies assessing the effect of early sub-symptom threshold exercise on VOM function recovery.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, dual-task effects have been noted previously in relation to postconcussion exercise: those who began supervised exercise within the first week of a concussion performed better on a dual-task gait evaluation than those who did not begin exercising soon after injury. 32 Thus, given the potential of exercise to influence both cognitive and motor outcomes, dual-task evaluations may be useful to determine recovery in the context of exercise treatment programs following a concussion.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown heart rate thresholds to be significantly lower in patients with prolonged recovery rates. 136,141 There is evidence that early controlled exercise does not adversely affect recovery, 137,[142][143][144] but the role and exact timing of exercise introduction in the acute management of SRC is still not completely understood. Recent studies have provided evidence that adolescent athletes who exercised within days of injury recovered significantly faster than those who did not exercise or were prescribed a stretching prescription.…”
Section: Aerobic Exercisementioning
confidence: 99%